Principles and practice of constraint programming : 20th International Conference, CP 2014, Lyon, France, September 8-12, 2014. Proceedings - O'Sullivan, Barry (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed conference proceedings of the 20th International Conference on Principles and Practice of Constraint Programming, CP 2014, held in Lyon, France, in September 2014. The 65 revised papers presented together with 4 invited talks were carefully selected from 108 submissions. The scope of CP 2014 includes all aspects of computing with constraints, including theory, algorithms, environments, languages, models, systems, and applications such as decision making, resource allocation, and agreement technologies.